Pemanfaatan Bunga Telang (Clitoria Ternatea L.) Sebagai infused Water Pencegah Diabetes Mellitus - Prihatiningtyas, Indah; Aulia, Jaya; Alif Anugerah, Muhammad; Layla Mahani, Aurellia; Novita Pasauran, Sirry (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Dumaring is a village located in Talisayan District, Berau, East Kalimantan. Dumaring Village has many natural resources, one of which is the butterfly pea flower (Clitoria ternatea) which is widely planted by the community as an ornamental plant. Butterfly pea flowers are known to have various health benefits. In this community service activity, we educate the people of Dumaring Village by conducting socialization of the health benefits of butterfly pea flowers and demonstrating the making of butterfly pea flower infused water as a health drink for people with hypertension and diabetes mellitus